Equine gastric ulcer syndrome in adult donkeys: Investigation on prevalence, anatomical distribution, and severity. (25th March 2017) - Sgorbini, M.; Bonelli, F.; Papini, R.; Busechian, S.; Briganti, A.; Laus, F.; Faillace, V.; Zappulla, F.; Rizk, A.; Rueca, F.
Summary: The study was performed on 39 live donkeys that underwent gastroscopic examination. The lesions were recorded in accordance with the European College of Equine Internal Medicine Consensus Statement guidelines. The presence of Gasterophilus sp. larvae was also recorded. Larvae were collected and identified to species level. Fisher's exact test was used to compare different prevalence values for sex, age, and anatomical distribution of lesions. Gastric lesions were present in 20/39 (51.3% [35.6–67%]) donkeys; 19/39 (48.7% [95% confidence interval = 33–64.4%]) were affected only by equine squamous gastric disease (ESGD), while 1/39 (2.6% [0–7.5%]) showed both ESGD and equine glandular gastric disease (EGGD), thus 95% of positive donkeys showed lesions located in the nonglandular mucosa. The ESGD grade was 0/4 (48.7% [33–64.4%]) in 19/39, 1/4 (12.8% [2.3–23.3%]) in 5/39, 2/4 (25.6% [11.9–39.5%]) in 10/39, 3/4 in 4/39 (10.3% [0.7–19.8%]) and 4/4 in 1/39 (2.6% [0–7.5%]) donkeys, respectively. The EGGD lesion was a mild depression in the ventral glandular fundus. ESGD was primary in all the donkeys included and lesions were located around the cardia and along the lesser curvature. Gasterophilus sp. larvae were present in all animals and were identified as third‐stage larvae of Gasterophilus intestinalis . No animals showed clinical signs of equine gastric ulcer syndrome (EGUS). No significant differences relating to sex, age or breed were found in the prevalence of EGUS in this study, while the proportion of donkeys affected by ESGD was statistically higher than those affected by EGGD. To the best of our knowledge, this is the first report on the gastroscopic evaluation of EGUS in live donkeys. Our results show a higher prevalence of EGUS in live donkeys than values previously reported by other authors in donkeys that were dead or had been subjected to euthanasia. The detection of third‐stage G. intestinalis larvae was not unexpected since these can be found in the stomach of equids throughout the year, and G. intestinalis has been reported as the most common Gasterophilus sp. in Italy.